2018
DOI: 10.1002/cam4.1485
|View full text |Cite
|
Sign up to set email alerts
|

LGR5 promotes epithelial ovarian cancer proliferation, metastasis, and epithelial–mesenchymal transition through the Notch1 signaling pathway

Abstract: Leucine‐rich repeat‐containing G protein‐coupled receptor 5 (LGR5) plays a vital role in the development of malignant tumors; however, its biological role and underlying mechanism in epithelial ovarian cancer (EOC) remain unclear. In this study, we aimed to investigate the biological function and clinical significance of LGR5 in human EOC. We evaluated LGR5 expression in EOC cell lines and tissues from ovarian cancer patients by qPCR, Western blotting, and immunohistochemical analysis. Cell proliferation, colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…We demonstrated that OPN3 could promote the EMT and tumor metastasis in LUAD. It has been previously reported that a variety of G‐protein coupled‐receptor proteins promote metastasis by affecting the EMT process of cancer cells, including in lung cancer . However, more studies are warranted to further explore the molecular mechanism of OPN3 in affecting the EMT of LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that OPN3 could promote the EMT and tumor metastasis in LUAD. It has been previously reported that a variety of G‐protein coupled‐receptor proteins promote metastasis by affecting the EMT process of cancer cells, including in lung cancer . However, more studies are warranted to further explore the molecular mechanism of OPN3 in affecting the EMT of LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Altered membrane potentials are known to induce cellular proliferation, migration, and apoptosis [ 31 ]. LGR5 is a member of glycoprotein hormone receptor sub-family, which has been demonstrated to regulate tumorigenesis and metastasis in EOC through Notch1 signaling [ 32 ]. The notch pathway is known to regulate the self-renewal and survival of CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 is a critical molecule in cisplatin treatment for EOC patients and its inhibition can be a potential strategy to address chemoresistance [ 72 ]. LGR5 promotes ovarian cell proliferation, progression, and EMT [ 32 ] and is associated with chemoresistance in cervical cancer [ 34 ]. In bladder cancer, PAX5/PTGS2 cascade is known to induce cisplatin resistance [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other works have supported this idea since LGR5 + seems to be related to progression of different cancers, such as colon [24], papillary thyroid [25], breast [26], and ovarian cancers [27] by promoting epithelial ovarian cancer proliferation, metastasis, and epithelial–mesenchymal transition (EMT). Furthermore, LGR5 is overexpressed in ovarian cancer tissue compared to normal tissue [28]. Moreover, it is well known that patients with endometriosis have a higher risk of developing ovarian cancer [29].…”
Section: Discussionmentioning
confidence: 99%